Development of a Mitochondrial Marker for Distinguishing Between Ulva linza and Ulva prolifera - Rui Zhai; Chengnuo Tang; Shuying Wang; Jing Ma; Xinshu Li; Guoqiang Chen; Juntian Xu (Journal of Marine Science and Engineering)
The green tide is the biggest ecological disaster in Yellow Sea in recent decades, and the species composition has varied from year to year. The ITS (internal transcribed spacer) sequence combined with 5S rDNA spacer are the mainstream molecular markers for green macroalgae. The former can perfectly distinguish the majority of Ulva spp. except the LPP (Ulva linza–procera–prolifera) complex, and the latter is used to distinguish U. linza and U. prolifera exactly based on the former. However, in practice, 5S rDNA spacer is difficult to amplify perfectly with universal primers, and this ultimately affects the experimental process. For this reason, we developed a stable mitochondrial marker for the distinction between U. linza and U. prolifera. The phylogenetic tree based on the mitochondrial rps2 (ribosomal protein S2) gene fragment can distinguish the LPP complex into two clades: U. linza and U. prolifera. Therefore, we concluded that the mitochondrial marker can be a great substitute for 5S primers to distinguish U. linza and U. prolifera.